2020
DOI: 10.1093/eurheartj/ehaa070
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids and risk of aortic valve stenosis: a Mendelian randomization study

Abstract: Aims Aortic valve stenosis is commonly considered a degenerative disorder with no recommended preventive intervention, with only valve replacement surgery or catheter intervention as treatment options. We sought to assess the causal association between exposure to lipid levels and risk of aortic stenosis. Methods and results Causality of association was assessed using two-sample Mendelian randomization framework through diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 51 publications
4
61
0
Order By: Relevance
“…Main features of CAVD pathogenesis include lipid accumulation, inflammation, fibrosis and calcification. Low-density lipoprotein (LDL) and lipoprotein(a) levels have been shown to be causally associated with aortic stenosis 2,3 . Patients with familial hypercholesterolemia (FH) displayed a 7.9 -fold higher risk for CAVD 4 .…”
Section: Menaquinone 4 Increases Plasma Lipid Levels In Hypercholestementioning
confidence: 99%
“…Main features of CAVD pathogenesis include lipid accumulation, inflammation, fibrosis and calcification. Low-density lipoprotein (LDL) and lipoprotein(a) levels have been shown to be causally associated with aortic stenosis 2,3 . Patients with familial hypercholesterolemia (FH) displayed a 7.9 -fold higher risk for CAVD 4 .…”
Section: Menaquinone 4 Increases Plasma Lipid Levels In Hypercholestementioning
confidence: 99%
“…We would like to thank the editors for the opportunity to respond to the letter by Jiang et al and to clarify aspects of our Mendelian randomization (MR) methodology. 1 We would also like to thank Jiang et al for their interest in our research and for raising issues in relation to methodology and statistical approaches. Jiang et al raised a question about the selection of a statistical method and concluded that based on the predefined algorithm, the best estimation for the univariate association between triglyceride and aortic stenosis should have been the weighted median.…”
mentioning
confidence: 99%
“…Lipoprotein (a) contains an LDL-like particle containing an apoB-100 particle [9]. In the report by Nazarzadeh et al, increased LDL-C but not HDL-C or TG correlated to aortic stenosis in 1,961 cases [7].…”
Section: Discussionmentioning
confidence: 98%
“…If not treated, symptomatic and severe AS may cause heart failure and sudden death, with an estimated annual mortality of 50% [2,3]. Numerous underlying mechanisms of calcified non-rheumatic AS have been reported, including: congenital valve anomalies, mechanical stress, ageing process, high body mass index, stress, hypertension, elevated lipoprotein (a), high low-density lipoprotein cholesterol (LDL-C), apolipoprotein (apo) deposition, and genetic polymorphism with chronic inflammation [2][3][4][5][6][7][8][9]. In the prospective Malmö Diet and Cancer Study the highest quartile of LDL-C was associated with more than a doubled risk of incident AS during 16 years of follow-up [4].…”
Section: Introductionmentioning
confidence: 99%